THE EXAMINATION OF THE PLANNING PROCESS IN DIEPSLOOT WITH REFERENCE TO SANITATION - Sekhonyane, Phillip Makubetse (My University, 2011)
The purpose of the research was to examine planning processes in Diepsloot in relation to provision for sanitation. The study was an explanatory study that through a qualitative approach sought to obtain information as to why delivery of services, in particular in Diepsloot has been unsatisfactory. The key findings from the research reveal that there is poor implementation of plans, and this is the result of lack of an integrated approach planning, poor community participation, internal conflicts and weak capacity at the local level
MM - P&DM
Keywords: Sanitation; Informal settlements